Investigation of the waveguide properties of a borehole and their use for acoustic measurements in situ - JAROSZEWSKA, Anna (Archives of Acoustics, 1982)
A method of measurement of the velocity of a shear wave travelling in the vicinity of a borehole, using its waveguide properties, is both analyzed and verified. In particular, by this method, the shear wave velocity is determined from the velocity of the so-called tube wave which corresponds to the zero frequency limit of the lowest radial mode of propagation in the fluid filling the borehole. Investigations of the necessary conditions to obtain a tube wave and of its propagation were performed on a laboratory model of a borehole and in boreholes in situ. The results obtained show the possibility of a practical use of the method investigated for the determination of the mean velocities of shear waves in the rock mass surrounding the borehole.